Effects of deep reactive ion etching parameters on etching rate and surface morphology in extremely deep silicon etch process with high aspect ratio. (December 2017) - Xu, Tiantong; Tao, Zhi; Li, Hanqing; Tan, Xiao; Li, Haiwang
This study empirically investigates the influences of several parameters on surface morphology and etch rate in a high-aspect-ratio silicon etching process. Two function formulas were obtained, revealing the relationship between the controlled parameters and the etching results. All the experiments were conducted on an inductively coupled plasma system, using a Bosch process. The tested trenches' width ranged from 15 to 1500 µm and their depth ranged from 50 to 500 µm, which covers nearly all the typical sizes of micromechanical devices in practical applications. The controlled parameters are etching chamber pressure, bias power, and gas flow rate. The parameters of surface morphology include sidewall angle, surface roughness, and sidewall condition. We tested how the controlled parameters can influence the surface morphology and etch rate and formulated assumptions to explain those relationships. Meanwhile, we utilized linear regression to obtain experiential function formulas of the relationships among etch depth, structure width, etching time, and passivation time, with a correlation coefficient higher than 0.99. Using these formulas, 12-µm-wide and 377-µm-deep (aspect ratio 31.4) trenches with sidewall angles of 89° were achieved. Additionally, this experience was applied as a critical structure in a gas turbine structure system.